2018
DOI: 10.1128/aac.02035-17
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility and Genotyping of Mycobacterium avium Strains That Cause Pulmonary and Disseminated Infection

Abstract: subsp. mainly causes disseminated infection in immunocompromised hosts, such as individuals with human immunodeficiency virus (HIV) infection, and pulmonary infection in immunocompetent hosts. However, many aspects of the different types of subsp. infection remain unclear. We examined the antibiotic susceptibilities and genotypes of subsp. isolates from different hosts by performing drug susceptibility testing using eight antibiotics (clarithromycin, rifampin, ethambutol, streptomycin, kanamycin, amikacin, eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Hosts and niches of sequenced isolates are shown in Additional file 1: Table S13. Uchiya et al [40] reported a significant difference in antibiotic susceptibility between EA1, EA2, and SC2 human isolates4. Uchiya et al [37] reported a difference in chromosome structure between TH135 (EA2) and Mah104 (SC2)5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hosts and niches of sequenced isolates are shown in Additional file 1: Table S13. Uchiya et al [40] reported a significant difference in antibiotic susceptibility between EA1, EA2, and SC2 human isolates4. Uchiya et al [37] reported a difference in chromosome structure between TH135 (EA2) and Mah104 (SC2)5.…”
Section: Discussionmentioning
confidence: 99%
“…3. Uchiya et al [40] reported a significant difference in antibiotic susceptibility between EA1, EA2, and SC2 human isolates…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This diversity of NTM subspecies represents a significant obstacle against successful treatment, and current therapies require prolonged treatment and often lead to insufficient clinical outcomes due to the lack of subspecies identification [16]. Therefore, identifying NTM at a subspecies level is an essential step prior to treatment [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…MAC pulmonary diseases are controlled by treatment with antibiotics that include macrolide-based multidrug therapy, comprising macrolides (clarithromycin or azithromycin) in combination with rifampin, ethambutol, aminoglycosides (streptomycin or amikacin) and ciprofloxacin [10,11]. However, emerging virulent strains are found to be resistant to these antibiotics [12].…”
Section: Introductionmentioning
confidence: 99%